The effect of Si/Al ratio and sodium silicate on the mechanical properties of fly ash based geopolymer for coating - Asif, A. (Trans Tech Publications Ltd, 2015)
The present study has been performed to see the effect of varying Si/Al ratio (1. 85 to 3) by using same concentration of NaOH and same solid/water ratio for the development of mechanical properties at 28 days of room temperature and also select the Si/Al ratio for coating application. The performance of the geopolymer was investigated on the basis of compressive strengthSEM along with EDS. Pure sodium hydroxide specimens displayed decreased strength. However the combination of sodium hydroxide and sodium silicate specimen with aSi/Al ratio of 2 showed maximum strength, whereas the specimen after Si/Al ratio 2 showed decrease in strength. Â© (2015) Trans Tech Publications, Switzerland.